First nosocomial cluster of COVID-19 due to the Delta variant in a major acute care hospital in Singapore: investigations and outbreak response - Lim, Wei Yen (2022)
Objectives: The first large nosocomial cluster of coronavirus disease 2019 (COVID-19) in Singapore in April 2021 led to partial closure of a major acute care hospital. This study examined factors associated with infection among patients, staff and visitors; investigated the possible role of aerosol-based transmission; evaluated the effectiveness of BNT162.b2 and mRNA1273 vaccines; and described the successful containment of the cluster. Methods: Close contacts of patients with COVID-19 and the affected ward were identified and underwent surveillance for severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection. Patient, staff and visitor cohorts were constructed and factors associated with infection were evaluated. Phylogenetic analysis of patient samples was performed. Ward air exhaust filters were tested for SARS-CoV-2. Results: In total, there were 47 cases, comprising 29 patients, nine staff, six visitors and three household contacts. All infections were of the Delta variant. Ventilation studies showed turbulent air flow and swabs from air exhaust filters were positive for SARS-CoV-2. Vaccine breakthrough infections were seen in both patients and staff. Among patients, vaccination was associated with a 79% lower odds of infection with COVID-19 (adjusted odds ratio 0.21, 95% confidence interval 0.05–0.95). Conclusions: This cluster occurred despite enhancement of infection control measures that the hospital had undertaken at the onset of the COVID-19 pandemic. It was brought under control rapidly through case isolation, extensive contact tracing and quarantine measures, and led to enhanced use of hospital personal protective equipment, introduction of routine rostered testing of inpatients and staff, and changes in hospital infrastructure to improve ventilation within general wards.